Perbandingan Hukum Mengenai Kewenangan Penyidikan Perkara Pidana Antara Kejaksaan Indonesia dengan Korea Selatan: (Berdasarkan Kitab Undang-Undang Hukum Acara Pidana dan Criminal Prosedure Act of South Korea) - Dini Mardhatillah; Muhammad Ramdan Al Musthafa (Perkara : Jurnal Ilmu Hukum dan Politik, 2024)
This research focuses on discussing legal comparisons regarding the authority to investigate criminal cases between prosecutors in Indonesia and South Korea based on the Criminal Procedure Code (KUHAP) and the Criminal Procedure Act of South Korea (CPASK) as the South Korean Criminal Procedure Code. The aim of this research is to compare the authority of the prosecutor's office in investigating criminal cases between Indonesia and South Korea, which is reviewed using the Criminal Procedure Code of each country. The research method used is normative legal research through a statutory approach. The results of the research concluded that the Prosecutor's Office in Indonesia is not given the authority by the Criminal Procedure Code to investigate criminal acts, but there is a gap provided by Law No. 16 of 2004 for the prosecutor's office to investigate specific criminal acts such as corruption and money laundering. As for general crimes, the prosecutor's office does not have the authority to carry out investigations because the position of the prosecutor's office is as a prosecuting agency. Meanwhile, in South Korea, the prosecutor's office is given the authority by CPASK to carry out criminal investigations, both general and specific, both directly and indirectly. Both have their respective advantages and disadvantages. In South Korea, it is considered more efficient in terms of time and costs as well as fast handling of cases because they are handled by the same agency and prosecutors have more control over criminal cases that are being handled specifically for follow-up to the prosecution and examination stages in court.